DIGITAL-BASED SUSTAINABLE MANAGEMENT TRANSFORMATION IN IMPROVING LEARNING SYSTEM AT STATE JUNIOR HIGH SCHOOL 1 INDRALAYA SELATAN - Reni Januarti; Zulkifli Sultan (ZILLZELL MEDIA PRIMA, 2026)
Digital transformation has become an important element in the development of sustainable education management in the current technological era. This research aims to describe how digital-based sustainable management is implemented in improving the learning system at State Junior High School 1 Indralaya Selatan. The approach used is descriptive qualitative with a case study method. Data was collected through semi-structured interviews with 10 participants consisting of the principal, teachers, administrative staff and school committee. The results showed that the school has adopted some digital practices, such as the use of online learning platforms and cloud-based administration systems, but the implementation is still partial and not fully integrated into long-term managerial policies. The main challenges include low digital literacy, limited infrastructure and the absence of consistent internal policies. Nonetheless, digitalization has been shown to improve learning effectiveness and school operational efficiency. This research recommends the need to strengthen human resource capacity, formulate comprehensive digital policies, and invest in infrastructure and collaboration among educators to support the sustainability of digital transformation in school management.